Ability distribution and dynamics of wage inequality: Unintended consequences of human capital accumulation - Kirill Borissov; Aleksey Minabutdinov; Roman Popov (ETH Zurich, CER-ETH - Center of Economic Research, 2024)
This study investigates the dynamics of between-group and within-group wage inequality in a model with heterogeneous learning abilities putting a key emphasis on the shape of the ability distribution. In our model, intergenerational human capital externalities incentivize individuals to invest in skills, consequently reshaping the composition of the labor force by expanding the proportion of skilled workers from the lower end of ability distribution. We show that if, in the process of human capital accumulation, the skill premium increases, then wage inequality among skilled workers, as measured by the Gini coefficient, also increases. For several common distributions of abilities, the composition effect contributes to an upward shift in the between-group inequality and inequality among skilled workers. We also demonstrate that the composition effect contributes to an increase in wage inequality when ability distributions are represented by empirical distributions of students' assessment scores.
Keywords: I24; J24; J31; 330; human capital; wage inequality; skill premium; composition effect